Siglec-1-positive plasmacytoid dendritic cells (pDCs) in human peripheral blood: a semi-mature and myeloid-like subset imbalanced during protective and autoimmune responses - Wilhelm, Theresa Rita; Taddeo, Adriano; Winter, Oliver; Schulz, Axel Ronald; Mälzer, Julia-Nora; Domingo, Cristina; Biesen, Robert; Alexander, Tobias; Thiel, Andreas; Radbruch, Andreas; Hiepe, Falk; Gerl, Velia (Clinical immunology, 2016)
Plasmacytoid dendritic cells (pDCs) play a central role in the pathogenesis of systemic lupus erythematosus (SLE) as IFN-α producers and promoters of T-cell activation or tolerance. Here, we demonstrated by flow-cytometry and confocal microscopy that Siglec-1, a molecule involved in the regulation of adaptive immunoresponses, is expressed in a subset of semi-mature, myeloid-like pDCs in human blood. These pDCs express lower BDCA-2 and CD123 and higher HLA-DR and CD11c than Siglec-1-negative pDCs and do not produce IFN-α via TLR7/TLR9 engagement. In vitro, Siglec-1 expression was induced in Siglec-1-negative pDCs by influenza virus. Proportions of Siglec-1-positive/Siglec-1-negative pDCs were higher in SLE than in healthy controls and correlated with disease activity. Healthy donors immunized with yellow fever vaccine YFV-17D displayed different kinetics of the two pDC subsets during protective immune response. PDCs can be subdivided into two subsets according to Siglec-1 expression. These subsets may play specific roles in (auto)immune responses.
Available online 7 December 2015
Gesehen am 11.02.2021